PENGARUH PEMBERIAN PAKAN TAMBAHAN DARI KOMBINASI TEPUNG CACING TANAH DAN TEPUNG AMPAS TAHU TERHADAP PERTUMBUHAN IKAN BETOK (Anabas testudineus) - Zainal Berlian; Fitratul Aini; Dinatul Aliah (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2015)
soil Worm and knowing Waste to own womb very high protein until Soil Worm and knowing Waste can to be used as the good addition food to betok's fish. with fish age betok 4 month Soil Worm Giving and knowing Waste to be expected can to level it growing to Fish Betok. this Research have go to know the influence of Soil Worm-giving and Waste Know in Fish growing Betok (Anabas testudineus) and to know foodwhich is to get it result that maximal in Fish growing Betok (Anabas testudineus). the Research is executed in Laboratory TO MIPA UIN Raden Fatah Palembang . This Research to use it Random Planing Complete (RAL) with 4 Treatment and 6 Repeating. The mentioned Treatment is P0= pelet, P1= knowing waste 8 gr and soil worm 4 gram, P2= knowing Waste 6 gr and soil worm 6 gr, P3= Soil Worm 8 gr and knowing waste 4 gr. show analysiical Result that growing grew highest to long of fish to treatment P3=4,36 cm and lowest 1,96 cm. To highest heavy to treatment P3= 4,76 gr, and lowest 1,5 gr. Its conclusion is Soil Worm giving and Waste Know to fish Betok (Anabas testudineus) influency in long growing and heavy of body betok's fish